Approaches to Leadership from the Perspective of Generation Z - Andreea Bianca ENE (CONSTANTIN); Claudiu Nicolae GHINEA; Andreea Simona SĂSEANU (Revista de Management Comparat International)
Generation Z poses a significant challenge for organizations, as its members express a clear preference for adaptive leaders who are capable of navigating change effectively. This generation, however, is poised to become the leaders of tomorrow. Regardless of generational affiliation, all individuals must possess a high degree of selfawareness to successfully adapt to future demands. This paper examines the leadership perspectives of Romanian high school students. The motivation behind this research stems from the contemporary relevance of Generation Z's views on leadership. A quantitative approach was employed, utilizing a structured survey to gather responses from high school students regarding their views on leadership. The objectives of this study include identifying the leadership style favoured by these students and exploring the factors that influence their leadership preferences. The survey was conducted online in February 2024 using Google Forms, and the data were analysed with Microsoft Excel and SPSS statistical software. I hope that the findings of this research will be valuable to those interested in this topic, particularly PhD students and others seeking a deeper understanding of Generation Z's approach to leadership